Unveiling the crystallographic origin of mechanochemically induced monoclinic to triclinic phase transformation in WO3. Issue 8 (10th February 2021) - Bandi, Suresh; Srivastav, Ajeet K.
Abstract : This study reports the anomalously stabilized low-temperature triclinic phase (δ-WO3 ) during high energy ball milling (HEBM) of the monoclinic γ-WO3 phase. Abstract : This study reports the anomalously stabilized low-temperature triclinic phase (δ-WO3 ) during high energy ball milling (HEBM) of the monoclinic γ-WO3 phase. The transformation evidenced unit cell contraction with distorted structural parameters resulted in a lower symmetry phase. The phase transformation was understood to be HEBM-induced pressure/compression involved atomic displacement and octahedral tilting-driven polymorphic transition. The major distortion/cooperative octahedral tilting occurred on the (020) plane of γ-WO3 parallel to the b axis. The crystallographic origin of such distortions and unit cell compression mechanisms are explained further. The obtained δ-WO3 phase was stable at room temperature owing to its nanocrystalline structure (11 ± 6 nm) that limits reversible and forward transformations of δ-WO3 → γ-WO3 and γ-WO3 → ε-WO3, respectively.